New species and a new genus of Hippotragini (Bovidae) from Makapansgat limeworks - Vrba, Elizabeth S (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1987)
A revision of the Hippotragini from the Makapansgat Limeworks is proposed : a new species of Hippotragus is described, Hippotragus cookei, and fossils previously referred to cf. Oryx gazella (Wells and Cooke, 1956) and Hippotragus gigas (Gentry and Gentry, 1978) are assigned to this species. H. gigas is present in the Pleistocene Member 5, but not in the Pliocene Grey Breccia, Member 3, as had been formerly supposed . A new genus and species from Member 3, Wellsiana torticornuta, tentatively referred to ?Hippotragini, is described based on a frontlet that had been assigned to Damaliscus sp. (aff. albifrons) by Wells and Cooke ( 1956). The horncore piece previously referred to Aepyceros cf. melampus (Wells and Cooke, 1956) may belong to the same species as ?Hippotragini sp. nov. (Gentry, 1986) from the Laetolil Beds, Tanzania. The hippotragine fossils here discussed again emphasize that Makapansgat Member 3 contains a Pliocene assemblage that is more ancient than was originally thought, with particular affinities with the Laetolil Beds and also with the Pinjor Formation of the Siwaliks in India and Pakistan.
Keywords: Pleistocene; Pliocene; Laetolil Beds; Member 3; Pinjor Formation